2021
DOI: 10.1101/2021.06.17.448784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Image quantification technique reveals novel lung cancer cytoskeletal phenotype with partial EMT signature

Abstract: Epithelial-mesenchymal Transition (EMT) is a multi-step process that involves cytoskeletal rearrangement. Here, using novel image quantification tools, we have identified an intermediate EMT state with a specific cytoskeletal signature. We have been able to partition EMT into two steps: (1) initial formation of transverse arcs and dorsal stress fibers and (2) their subsequent conversion to ventral stress fibers with a concurrent alignment of fibers. Using the Orientational Order Parameter (OOP) as a figure of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Image quantification can also reveal specific cytoskeletal attributes of hybrid E/M phenotypes. On treatment of NSCLC cells A549, H460 and H1299 with TGFβ, stress fibers increasingly aligned well among themselves, as reflected by a gradual change in the orientational order parameter [48]. Cells in partial or early EMT (14 h posttreatment) stage had fewer spots for focal adhesion kinases (FAKs) but stress fibers in late EMT (48 h post-treatment, i.e.…”
Section: Cytoskeletal Hallmarks Of Hybrid E/m Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Image quantification can also reveal specific cytoskeletal attributes of hybrid E/M phenotypes. On treatment of NSCLC cells A549, H460 and H1299 with TGFβ, stress fibers increasingly aligned well among themselves, as reflected by a gradual change in the orientational order parameter [48]. Cells in partial or early EMT (14 h posttreatment) stage had fewer spots for focal adhesion kinases (FAKs) but stress fibers in late EMT (48 h post-treatment, i.e.…”
Section: Cytoskeletal Hallmarks Of Hybrid E/m Phenotypesmentioning
confidence: 99%
“…Atomic force microscopy measurements revealed that the Young's modulus of the 'nest-like' partial EMT cells was intermediate to that of untreated and late stage EMT. Although the time-period for which cells were treated with TGFβ may seem insufficient to induce a complete EMT, but E-cadherin was drastically reduced both at mRNA and protein levels [48]. However, how loss of E-cadherin and the cytoskeletal changes can impact each other, needs further analysis.…”
Section: Cytoskeletal Hallmarks Of Hybrid E/m Phenotypesmentioning
confidence: 99%